Endolymphatic Hydrops in Patients With Intralabyrinthine Schwannomas - Zhang, Yibo; Li, Feitian; Dai, Chunfu; Wang, Wuqing (Frontiers in Surgery, 2021)
Abstract Purpose The presence of endolymphatic hydrops (EH) in patients with intralabyrinthine schwannomas (ILSs) is poorly understood. This study aims to determine whether there is a correlation between endolymphatic hydrops and clinical presentations of ILS. Methods Data from nine patients with ILSs were retrospectively reviewed between 2007 and 2020. Temporal bone MRI with intratympanic or intravenous injection of gadolinium was applied to detect ILSs and EH. Results 3D-real inversion recovery (IR) sequence MRI of the temporal bone confirmed ipsilateral EH in 4 patients (4/6). All 4 patients with EH on MRI presented with vertigo similar to Meniere’s disease. Among these patients with EH, 1 patient with EH in the cochlea showed moderate sensorineural hearing loss, while 3 patients with EH in both the vestibule and cochlea showed profound hearing loss. MRI demonstrated a transmacular tumor (TMA) in 1 patient, intravestibular (IV) in 4 patients and vestibulocochlear (VC) in 4 patients. Two IV cases showed moderated hearing loss, while the TMA and VC cases showed profound hearing loss. Transotic resection of the tumor was applied in 5 patients; translabyrinthine resection was applied in 1 patient; 2 patients were under observation; and 1 patient was given intratympanic injection of gentamicin (ITG). During follow-up, all of the treated patients reported relief of vertigo and postoperative MRI was performed in 2 patients which showed no tumor recurrence. The two patients under observation showed no deterioration of hearing loss or vertigo. One patient was lost to follow-up. Conclusion EH concurrent with ILSs has been underestimated previously. With the extensive application of temporal bone MRI paradigms, such as 3D-real IR sequence MRI, more cases of potential EH in patients with ILS will be identified. The severity of hearing loss may be associated with the location of the tumor and the degree of EH. Keywords Intralabyrinthine schwannomas (ILSs); Endolymphatic hydrops; Vertigo; Hearing loss; MRI